Collection of Taxes by Hostage-Taking on Islamic Law Perspective - Fitri Raya (Fakultas Syariah UIN Sultan Maulana Hasanuddin Banten, 2022)
One of the government's revenues is to fill the state treasury through tax collection, because taxes make a large contribution to the state, to meet the needs of the community through the state treasury. In other words, tax is an agreement born from a law that obliges a person who has met the requirements specified in the law to pay a certain amount to the state that can be enforced, without getting compensation that is directly used to finance the administration of the state. Efforts to collect taxes are certainly important, so it should be understood that from an economic perspective, taxes are a transfer of wealth from taxpayers to the state treasury, which can be seen as a reduction in wealth. Because taxes reduce wealth, naturally someone (taxpayers) will try not to fulfill these obligations, by avoiding taxes or not paying taxes. The non-fulfillment of tax obligations can occur because the taxpayer or the tax underwriter does not have the will or intention to fulfill their tax obligations. The indifference of taxpayers in paying taxes makes the competent authorities forced to collect in the ways that have been stipulated in the law, one of which is by means of hostage. In this paper, we will explain tax collection by means of hostage taking in the perspective of Islamic law.